Genetics of adaptation in domestic farm animals: a review - Mirkena, T.; Duguma, G.; Haile, Aynalem; Tibbo, Markos; Okeyo Mwai, Ally; Wurzinger, Maria; Sölkner, Johann (Elsevier, 2010)
This review summarizes available information on genetics of adaptation in major livestock species focusing on small ruminants. Adaptation to humans and consequences of domestication on predator aversion, mechanisms of adaptation to available feed and water resources, severe climates and genetic evidence of disease tolerance or resistance have been presented. The latter focuses on gastrointestinal parasites and bacterial diseases. The resource allocation by the animal to production and fitness traits under both optimal and sub-optimal conditions has a genetic background. Such information would help in identifying the most appropriate and adapted genotypes capable of coping with the environmental challenges posed by the production systems or, wherever possible, in adapting the environments to the requirements of the animals.